Managing Dead Stock Spare Part Using House of Risk Framework - Muhammad Saiful Hakim; Immanuel Rio Atmaja; Imam Baihaqi (International Journal of Supply Chain Management, 2018)
House of risk framework had been applied widely for identify root cause of problem in supply chain. However, house of risk framework usage to mitigate problem in spare part stocks are still limited. In this paper we employ house of risk Framework to identify root cause of problem in spare parts stock (dead stock). The result of this research could be used as comparison of house of risk framework in spare parts stocks. With a eminent confidence, house of risk framework suggest several factor that contribute to dead stock namely: spare part user, time limit in inventory, mismatch inventory data. House of risk also suggest corrective action needed to resolve this problem, such as promoting regulation conformity for spare part usage and inventory, and assign budget for each stock users to track and control spare part consumption for each users.